RESPONSABILIDADE DA ENGENHARIA CIVIL FRENTE AO IMPACTO AMBIENTAL NEGATIVO DECORRENTE DA EXECUÇÃO DE OBRAS DE INFRAESTRUTURA: RESPONSIBILITY OF CIVIL ENGINEERING IN ADDRESSING NEGATIVE ENVIRONMENTAL IMPACT RESULTING FROM INFRASTRUCTURE CONSTRUCTION (REMUNOM, 2025)
Infrastructure construction is crucial for the economic development of a region or country, but it is important to consider the environmental impacts that these works can cause. The objective of this work is to present the importance of analyzing the responsibility of Civil Engineering in addressing these environmental impacts and how infrastructure works can negatively affect the environment. Specific objectives include presenting the ethical aspects involved, describing the applicable environmental norms and legislation, discussing environmental impact assessment, environmentally responsible technologies, and practices. For this study, a bibliographic review methodology was adopted. Thus, the research encompassed an extensive consultation of resources available on various platforms, including Scielo, Google Scholar, and the open-access portal of a network of university libraries. Additionally, specialized articles published in civil engineering journals were analyzed. The selection of materials included publications from the last 10 years, with the aim of ensuring the relevance and timeliness of the analyzed data. In conclusion, the ethical responsibility of civil engineering involves a comprehensive approach to environmental conservation and sustainability. By adopting sustainable practices, following environmental standards, and implementing mitigation measures, civil engineers can significantly contribute to minimizing negative environmental impacts associated with infrastructure development. It is imperative that professionals and regulatory bodies collaborate effectively, prioritizing environmental protection and adopting sustainable practices to ensure a harmonious balance between infrastructure development and environmental preservation.Keywords: Civil engineering; Responsibility; Negative environmental impact.